Typifying rural landscapes of the suburban district of Odesa - Valentyna Oliinyk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The main reasons for changing landscapes in the suburbs should be called: excessive unjustified use of natural resources: soil, reservoirs, forests; soil and water pollution; removal of garbage and waste from cities to unorganized landfills; non-compliance with crop rotation rules; improperly applied mineral fertilizers and pesticides; extremely high anthropogenic load on individual territories. This study can serve as a starting point for the formation of typology, planning the development of suburban territories, including the development of tourism within them. We consider it appropriate not only the selection of the types of rural landscapes of the suburbs, but also conduct appropriate zoning, given its features and landscape types for sustainable management, conservation and restoration of natural resources (land, water, forest), efficient use of land taking into account geoecological situation. Elements of the rural natural landscape have the great significance for the residents of the city and suburban area in terms of their functionality, sanitary, aesthetic and environmental criteria. Counting the huge influence of the city on the socio-economic development of the suburban area, there are huge changes in the natural environment of the suburb, rural landscapes, which perform various functions, which determines the need for their study, accounting, evaluation, protection and conditions of transformation. The article analyses approaches to the study of types of rural landscapes, criteria for their typing, taking into account economic (agricultural), social (population density, pendulum migration) and environmental (fertility, soil degradation, man-made load) indicators. As a result of the study, the types of rural landscapes of the suburbs of Odesa were determined: disturbed landscapes (geographically these landscapes are located in close proximity to the city border and are characterized by active construction, including elite cottage buildings, a large percentage of pendulum migrations, industrial and infrastructural functions and a small number of recreational facilities); degraded (neglected landscapes-characterized by eroded soils, with low yields. There are abandoned plots of countryside house cooperatives. There are slopes, ravines, and gullies in the terrain); agricultural (occupy almost half of the territory of the adjacent administrative districts. The zone of influence of the city has become a prerequisite for active farming, development of processing industry); recreational (valuable – are formed mainly from water and forest resources with recreational objects aimed at the development of tourism.